Dismantling the ‘Master’s’ House’: A Critical Examination on the Effect of a Racialised Identity on the Mental Health of People of African Descent in 21st Century Britain - Pilgrim, Niquita (2024)
This thesis introduces a transdisciplinary framework to unveil the impact of racialised identity on the mental health of individuals of African descent, challenging the dominance of Eurocentric methodologies in conventional psychological approaches. Established methods, including Cognitive Behavioural Therapy and related psychotherapeutic approaches, disproportionately reflect Eurocentric paradigms and knowledge systems, often neglecting the pervasive influence of structural racism and its profound psychological consequences. This Eurocentric bias poses clinical risks and hinders equality in access, treatment, and outcomes. Eurocentric approaches tend to oversimplify the experiences of individuals of African descent, characterising them as 'abnormal' and 'irrational' compared to white European standards. Practitioners guided by these approaches may overlook critical situational, spatial, and relational factors contributing to mental health disorders among African-descended populations, resulting in misinterpretations and misdiagnoses, obscuring the determinants of mental ill health among those racialised as 'Black.' Recognising the inadequacy of the mental health system for individuals of African descent, this thesis critically examines Eurocentric biases in scholarship concerning their thoughts and behaviours. Focused on twenty-first-century Britain, the research explores how these ideologies have permeated societal structures and institutions, fostering the normalisation of anti-Black/African sentiments within health and social care. To comprehensively assess the clinical and psychological implications of anti-Black/African racism, this thesis amplifies the voices of mental health professionals providing psychosocial therapeutic interventions to African-descended individuals. Adopting an intersectional approach, the research combines insights from participants with cultural studies, critical race and decolonial theories, history, and social psychology, proposing a more inclusive framework to supplement existing scholarship on the complex interplay between the human mind, behaviour, and anti-Black/African racism.